Pembelajaran Aplikasi Pengukur Kandungan Klorofil pada Daun Tanaman Padi: Oryza sativa L. - Saragih, Wismaroh Sanniwati (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Rice is a staple food in Indonesia, so the demand continues to increase along with the population growth. Rice cultivation in Indonesia is known for two planting systems, namely wetland rice which requires water and upland rice which is planted in fields without requiring special irrigation. Several regions in Indonesia have almost extinct upland rice varieties, such as the Fakhaito variety or black rice from Nias Regency, with a plant age of up to six months until harvest. Upland rice productivity is very low, affecting farmers' income, accompanied by suboptimal fertilization technology. This research aims to provide learning to students in using the SPAD-502Plus chlorophyll meter to detect the growth and health of upland rice plants from Nias. The results of the study show that treatment with liquid organic fertilizer correlates positively with leaf color, where the amount of chlorophyll is higher in the very green leaves of rice, and conversely the amount of chlorophyll decreases in plants with reduced greenness. The use of the SPAD-502Plus chlorophyll meter is a faster, non-destructive, comfortable, and non-disruptive way to measure plant growth, as the measurement is done directly.